Mídia, crítica e informação: a história pelas reportagens do posição, um jornal feito para o leitor - Amaro, Jonathan Neves (2024)
This dissertation seeks to investigate the trajectory of alternative journalism during the Brazilian military dictatorship, having as its object the newspaper Posição (1976-1979). Founded by journalists, the publication marked an era with its scoops and major reports on the Espírito Santo scene. Understanding alternative journalism as a territory of knowledge capable of influencing the way people see space and time, based on the hypothesis that the position, by adopting a critical stance, wrote and rewrote History, giving a voice to those who did not have one, opening space for opposition and, thus, participating in the deconstruction of the facts created until then. To do this, we draw a timeline of how the trajectory of the alternative proceeded to understand how the potentialities allowed by alternative journalism are explored in the reports that circulated between October 1976 and March 1979. Among the components, we must that the alternative, at the to focus on common issues at the time, distributing relations between media and history based on the pages and statements of sources, pointing to silenced and often hidden issues, as a counterpoint to the government's official discourse.